Analisis Faktor-Faktor yang Memengaruhi Turnover Intention (Studi Kasus Pada Divisi News Gathering Mnc Media) - Gunawan, Endang; Sukmawati, Anggraeni; Vitayala, Aida (Jurnal Manajemen Teori dan Terapan| Journal of Theoretical and Applied Management, 2019)
This study to analyze the effect of workload on turnover intention, workload on job satisfaction, competence on job satisfaction, competence on turnover intention, training on job satisfaction and job satisfaction on turnover intention. Data was collected through interviews using a questionnaire. Respondents in MNC Media division news gathering employees numbered 202 people. The analytical method used in this study is Structural Equation Modeling (SEM) which is processed using AMOS 22. The results of this study indicate that workloads have a significant effect on decreasing job satisfaction. Besides that the workload increases the desire to get out of work or company. Training has the effect of increasing job satisfaction from employees towards their employment. Employee competencies are known to have a positive influence on satisfaction but negative on turnover intention. While job satisfaction has a positive influence on turnover intention, the lower the job satisfaction, the higher the desire to get out.